Plan de marketing de la empresa mecánica Paredes de la ciudad de Nueva Loja, en el periodo 2013 – 2014 - Paredes Moya, Rocío Alejandra (2015)
This thesis entitled MARKETING PLAN MECHANICAL COMPANY CITY WALLS NEW Loja, IN THE PERIOD 2013-2014, has as main objective to develop a marketing plan for the company Mechanical Paredes, enabling the identification of business objectives get detailing strategies and actions to be performed to achieve in one year, it is reasonable to try to maximize profits and reduce costs, therefore it is necessary to improve the planning and organization within the company, with the sole purpose to submit to the owner a tool that facilitates control and is helpful for decision-making and administrative wise direction thereof. Also, this work has had its full theoretical foundation that has served to strengthen the information obtained; the methods used are: inductive, deductive, descriptive, analytical and statistical; techniques were used to collect data are set out below: An interview applied the Manager of the company's strengths and weaknesses identified, survey applied to 219 customers and 10 employees, which allowed them to perform internal analysis of the company; between the main results were obtained: In its evaluation of external factors of the company through the matrix of External Factors Evaluation of the weighted score was 2.47 which means that there are great advantages given the market in which the company Mechanics develops and Paredes threats currently facing, is not taking advantage of opportunities that arise, there are threats that must be overcome and opportunities to exploit. The evaluation of internal factors of the company, made through the evaluation matrix of internal factors as weighted result gave 2.47 which means that our strengths have great weight in the evaluation but we have weaknesses that need to be addressed and resolved as early as possible. Finally after having performed the analyzes was determined as central proposal four strategic objectives: Provide the free checkup loyal customers, vehicle pre-review. Develop an advertising plan to attract new customers. Efficient use of technology resources available to the Company Mechanics Paredes. Establish a continuous training program to employees. These strategic objectives are designed to encourage the activities of marketing, sales and promotion of services and products offered with the same budget totaling the amount of $ 13.497,00; which is designed to do so within one year. Besides raising mission, vision and values and business philosophy for the company Mechanical Paredes